A PRAGMATIC STUDY OF COOPERATIVE PRINCIPLES AND GRICE’S MAXIMS IN NOVEL “THE SECRET GARDEN” BY FRANCES HODGSON BURNETT - Rika Septi Cahyani; Budiati Budiati (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2022)
This research analyzes a novel by Frances Hodgson Burnett entitled “The SecretGarden” using a theory of cooperative principle from Paul Grice. The study aims tofind out the violation of maxims that emerged in the novel. This research used adescriptive qualitative method, in which the researcher takes a note and pins someconversation in the novel that contains a maxim violation. The results of thisresearch show that it is found violations of maxims; maxim of quantity, maxim ofquality, maxim of relevance, and the last one is maxim of manner. The most floutedmaxim which fails to observe is maxim of quantity from all data found. The datashow as the following; maxim of quantity is 32%, maxim of quality is 11%, maximof relevance is 20% and maxim of manner is 27% in average percentage 100% intotal 102 data. From this research, it can be concluded that the existence of aviolation of the maxims in this novel is the aim of the writer to make humor thatrefers to something funny for the readers while reading the novel